2023
DOI: 10.3390/electronics12081816
|View full text |Cite
|
Sign up to set email alerts
|

An Edge Intelligent Method for Bearing Fault Diagnosis Based on a Parameter Transplantation Convolutional Neural Network

Abstract: A bearing is a key component in rotating machinery. The prompt monitoring of a bearings’ condition is critical for the reduction of mechanical accidents. With the rapid development of artificial intelligence technology in recent years, machine learning-based intelligent fault diagnosis (IFD) methods have achieved remarkable success in the field of bearing condition monitoring. However, most algorithms are developed based on computer platforms that focus on analyzing offline, rather than real-time, signals. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…To verify the effectiveness of the proposed method, it was compared with the different methods: DBN, IG-CWT-CNN [31], TF-MDA [32], ICPW-HPF-CNN [33], ML [34], JDA [35], TCA-DBN [36], DSAN [18], and S-Alexnet [37]. The structure of the DBN was [80,40,40,20], and the learning rate was 0.05.…”
Section: Test Imentioning
confidence: 99%
“…To verify the effectiveness of the proposed method, it was compared with the different methods: DBN, IG-CWT-CNN [31], TF-MDA [32], ICPW-HPF-CNN [33], ML [34], JDA [35], TCA-DBN [36], DSAN [18], and S-Alexnet [37]. The structure of the DBN was [80,40,40,20], and the learning rate was 0.05.…”
Section: Test Imentioning
confidence: 99%
“…The results consistently demonstrated that the proposed method outperforms existing state-of-the-art techniques in terms of diagnostic performance. Ding et al [33] proposed an intelligent edge diagnosis method based on parameter transplantation in convolutional neural networks (CNN). Verification using the CWRU dataset revealed an average prediction accuracy of 94.4% on the test set with this approach.…”
Section: Diagnostics Based On Transfer Learning From Different Device...mentioning
confidence: 99%
“…Except for machine learning methods, deep learning methods have been widely applied to prognostics for health monitoring in recent years. As a classic deep learning method, a convolutional neural network (CNN) utilizes the advantages of multiple neural layers to represent input data in feature values and reduce higher numbers of dimensions and improve prognostic recognition [ 25 , 26 , 27 , 28 , 29 ]. However, CNNs suffer from overfitting, exploding gradients, and class imbalances that reduce recognition performance.…”
Section: Introductionmentioning
confidence: 99%